Relationship Between HR Quality Management and Alfamart Customer Satisfaction Level (Case Study of Alfamart Cempaka Putih, Jakarta - Novi Novaria; Agus Setiono; Irfan Rusydi Triyanto; M Badrun Tamam (JURNAL ILMIAH EDUNOMIKA, 2023)
TAt Alfamart Cempaka Putih Minimarket, Jakarta, the purpose of this study is to identify and examine the dimensions of human resource quality related to customer satisfaction. The participants in this study were all Alfamart Cempaka Putih Minimarket customers. This indicates that the correlation is quite close and that Ho is rejected at a significant level of 0. This indicates that the correlation is quite close and that Ho is rejected at a significant level of 0. On the other hand, H1 indicates that there is a relationship between the quality of human resources and customer satisfaction with an RS value of 0. On the other hand, H1 indicates that there is a relationship between the quality of human resources and customer satisfaction with an RS value of 0. On the other hand, H1 indicates that there is a relationship between the quality of human resources and customer satisfaction with an RS value of 0. On the other hand, H1 indicates that there is a relationship between the quality of human resources and customer satisfaction with an RS value of 0. On the other hand, H1 indicates that there is a relationship between the quality of human resources and customer satisfaction with an RS value of 0.632.